Dual drug-loaded halloysite hybrid-based glycocluster for sustained release of hydrophobic molecules. Issue 91 (14th September 2016) - Massaro, M.; Riela, S.; Baiamonte, C.; Blanco, J. L. J.; Giordano, C.; Lo Meo, P.; Milioto, S.; Noto, R.; Parisi, F.; Pizzolanti, G.; Lazzara, G.
Abstract : A dual drug-loaded HNT–CD glycocluster delivery system based on halloysite nanotubes and carbohydrate functionalized cyclodextrin for delivery of natural drugs was developed. Abstract : A dual drug-loaded HNT–CD glycocluster delivery system based on halloysite nanotubes and carbohydrate functionalized cyclodextrin was developed by a green protocol using solvent-free microwave irradiation. The nanohybrid was employed for concurrent load and release of silibinin and curcumin. The new delivery system was characterized by means of TGA, FT-IR spectroscopy, SEM and DLS. These techniques confirm the successful loading of the two drugs in the system. SEM and DLS measurements highlighted that the nanomaterial preserves a tubular structure with an average hydrodynamic radius of ca. 200 nm. The release of the drugs from the HNT glycocluster was investigated by means of UV-vis spectroscopy at two different pH values simulanting the typical physiological conditions of either gastric or intestinal fluids. Enzyme-linked lectin assays (ELLA) demonstrated that highly mannoside–cyclodextrins HNT entities display high affinity towards mannose selective ConA lectin. Biological assays showed that the new drug delivery system exhibits anti-proliferative activity against the investigated cell lines. Fluorescence microscopy confirmed ELLA results and it showed a high propensity of this drug delivery system to cross cell membranes and to penetrate into the cell nucleus. The results revealed that the synthesized multicavity system is a material of suitable size and nanoarchitecture to transport drugs into living cells.